Fraud diamond analysis of financial statement fraud - Ingga medlar; Haryono Umar (Enrichment : Journal of Management, 2023)
The purpose of this study is to determine Fraud Diamond Analysis of Fraud Financial Statements. The type of data used in this research is secondary data. The data used in this study were obtained from www.idx.co.id, the company's website and the Indonesian Capital Market Directory (ICMD). The population in this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for 2018-2020 and processed using the IBM SPSS application and analysis using a purposive sampling technique. Based on the results of the study, empirical facts were obtained in the form of: 1) There is a significant positive (unidirectional) influence between pressure on fraudulent financial statements; 2) There is a significant positive (unidirectional) effect between opportunity and financial reporting fraud; 3) There is a significant positive (unidirectional) effect between rationalization and fraudulent financial reporting; 4) There is a significant positive (unidirectional) effect between capability and financial statement fraud.